Racial and Socioeconomic Disparities in Oral Disadvantage, a Measure of Oral Health-related Quality of Life: 24-month Incidence - L. Scott Chavers, MPH; Gregg H. Gilbert, DDS, MBA; Brent J. Shelton, PhD (Blackwell Synergy, 2002)
This paper estimates the incidence of oral disadvantage based on the subject’s approach to dental care, sex, race, and financial status; identifies demographic and socioeconomic characteristics that were associated with oral disadvantage; and determines if these characteristics were differentially associated with the three domains of oral disadvantage